Pivotal role of levoglucosenone and hexadecanoic acid from microalgae Chlorococcum sp. for corrosion resistance on mild steel: Electrochemical, microstructural and theoretical analysis - Rai M.P.; Khanra A.; Rai S.; Srivastava M.; Prakash R. (My University, 2025)
A green and holistic approach is proposed for inhibitive performance of methanolic extract of microalgae Chlorococcum sp. (MEC), effectively contributed by levoglucosenone and hexadecanoic acid for corrosion resistance on mild steel under acidic environment. Inhibition properties of these bioactive compounds are demonstrated by gravimetric (weight loss), electrochemical (Tafel polarization, impedance spectroscopy) and surface morphological analysis (scanning electron microscopy and atomic force microscopy) that support excellent adsorption potential. The maximum inhibition efficiency is obtained ~96% at 11.7 ppm MEC in 1 M HCl at 303 K. The theoretical calculation is investigated by Density Functional Theory (DFT) to understand the intra molecular charge transfer in aqueous environment as well as the electrostatic interaction between inhibitor molecules and metallic surface. Microstructural analysis is carried out to corroborate the consequence of surface corrosion at different time interval up to three days consecutively. The inexpensive inhibitor extracted from Chlorococcum sp., exhibited an enormous strength for large scale utilization in metal corrosion inhibition under acidic medium. © 2018 Elsevier B.V.